Neuropharmacological effects of essential oil from the leaves of Croton conduplicatus Kunth and possible mechanisms of action involved. (15th July 2018) - Oliveira Júnior, Raimundo Gonçalves de; Ferraz, Christiane Adrielly Alves; Silva, Juliane Cabral; de Andrade Teles, Roxana Braga; Silva, Mariana Gama; Diniz, Tâmara Coimbra; dos Santos, Uiliane Soares; de Souza, Ana Valéria Vieira; Nunes, Carlos Eduardo Pereira; Salvador, Marcos José; Lorenzo, Vitor Prates; Quintans Júnior, Lucindo José; et al.
Abstract: Ethnopharmacological relevance: Croton conduplicatus Kunth (Euphorbiaceae) is a Brazilian aromatic medicinal plant, widely known as "quebra-faca". In folk medicine, its leaves and stem-barks are used as a natural analgesic for the treatment of headaches. Aim of the study: In this study, we describe for the first time the neuropharmacological potential of the essential oil obtained from the leaves of Croton conduplicatus (EO) in experimental models of pain, anxiety and insomnia. The mechanisms of action involved in these activities were also investigated. Material and methods: Different experimental models were used to evaluate the antinociceptive (acetic acid, formalin-induced nociception and hot plate tests), anxiolytic (elevated plus maze and hole board tests) and sedative (thiopental-induced sleeping time) effects of EO in mice. EO was evaluated in three different doses (25, 50 and 100 mg/kg, i.p.) and compared with positive and negative controls in all experimental protocols. When appropriate, animals were pretreated with pharmacological antagonists (naloxone, atropine and flumazenil) in order to evaluate the mechanisms of action involved. A docking study also was performed to identify possible targets involved. Results: EO (25, 50 and 100 mg/kg, i.p.) demonstrated a significant antinociceptive activity in all experimental models. Pretreatment with naloxone or atropine reversed the antinociceptive response ( p  < 0.05), suggesting the involvement of opioid and muscarinic receptors, respectively. A docking study was performed with the major components identified in EO (1, 8 cineole − 21.42%, spathulenol – 15.47%, p -cymene – 12.41% and caryophyllene oxide – 12.15%), demonstrating favorable interaction profile with different subtypes of muscarinic (M2, M3 and M4) and opioids (delta and mu) receptors. EO also showed anxiolytic (mainly at doses of 25 and 50 mg/kg, i.p.) and sedative (only at the dose of 100 mg/kg, i.p.) effects in mice. These pharmacological responses were reversed by flumazenil ( p  < 0.05), indicating possible involvement of GABAA receptors. Conclusion: Our findings support the traditional use of this plant as a natural analgesic and suggest that EO is a multi-target natural product, presenting not only antinociceptive effect but also anxiolytic and sedative activities depending on the dose used. Graphical abstract: